Institutional Quality and the Investment Climate in Algeria: An Assessment of Constraints on Economic Attractiveness - Moussa MAAMRI; Yanis IDIRI; Hocine IFOURAH (Journal of Excellence for Economics and Management Research, 2026)
This paper analyzes the role of institutions and the business climate in enhancing investment attractiveness in Algeria, highlighting their potential contribution to economic growth and economic diversification. The main objective is to examine how institutional quality and the business environment influence the ability of the Algerian economy to attract investment and improve its economic performance.From a theoretical perspective, the study relies on the contributions of the new institutional economics, which emphasizes the fundamental role of institutions in organizing economic activity. Through formal and informal rules that govern economic interactions, institutions help reduce uncertainty, secure transactions, and improve market efficiency. In this context, governance quality, regulatory stability, and institutional transparency are considered key determinants of the investment climate.From an empirical perspective, the research examines the evolution of the business climate and institutional quality indicators in Algeria using international indicators related to economic governance, business creation, access to credit, and investor protection. The findings show that despite several reforms implemented in recent years, the Algerian economy still faces institutional and administrative constraints that may limit investment attractiveness.The study also highlights the strong dependence of the Algerian economy on the hydrocarbon sector, emphasizing the need to strengthen economic diversification policies and improve the business environment. In this regard, enhancing institutional quality, simplifying administrative procedures, and improving access to financing appear to be key mechanisms for promoting productive investment and supporting sustainable economic development.